1 - Du rapport Pearson (1970) au rapport Brandt (1980) ou la crise de l'idéologie du développement - Amin, Samir (Africa Development, 1980)
The World System is undergoing a structural crisis. Samir Amin's purpose in this article is to re-examine the solutions proposed in the report of the Brandt Commission, particularly as regards the North-South relations. He first states that this crisis is the normal resultant of changes in the economic and political power relations during the 1945 — 1970 period growth. The Third World countries entered the crisis as victims of extroverted development. The crisis, because it is global, is consequently a crisis of the theory of development. The author then criticizes the theoretical principles which underpin the proposed solutions. Thus, analysing these solutions in agriculture, he first points out that the priority given to it is rather superficial because it recommends the reduc tion of food priorities to food projects without reconsidering the overall licy of world integration. Such measures would only sharpen the poverty the peasants. As for industry, he shows that the success of the «New Indus trialized Countries» as defined in the report is certainly not in terms of the incomes of the workers and of the peasants; neither is it in terms of the social policy of these countries since it is a repressive one. The priority given to export industry does not in any case improve the foreign trade balance of these countries; the proof being that these are the most indebted countries. He then discusses issues such as Transnational (about which the comments of the report are limited to the idea of a code of conduct), inter national migrations (which contrary to what is said in the report, are not always advantageous to the countries) and the imminence of a financial breakdown which would be more likely caused by the erratic liquidities of transnational (which are more than those of the petroleum exporting coun tries) than the world inflation. The author then draws the conclusion that the solutions proposed in the report are incoherent, naive and impossible. Any strategy oriented towards a genuine ideology of development should give priority to the fol lowing: a self-centered development at the national and collective level; a restructuring of industry which would be at the service of agricultural development. For the author, the salvation lies in a maximum delinking of the Third World from the World System.